Experimental determination and model correlation for the solubilities of trialkyl phosphates in supercritical carbon dioxide. Issue 56 (25th May 2016) - Pitchaiah, K. C.; Sivaraman, N.; Lamba, Neha; Madras, Giridhar
Abstract : The solubilities of a series of trialkyl phosphates in supercritical carbon dioxide have been investigated. Abstract : The solubilities of a series of trialkyl phosphates in supercritical carbon dioxide have been investigated. The solubility measurement was carried out using a dynamic flow method. The measurements were performed at 313, 323 and 333 K and in the pressure range of 10 to 25 MPa. The trialkyl phosphates were found to be highly soluble in supercritical carbon dioxide and the solubilities were in the range of 0.01 to 0.1 mol fraction. The solubility of trialkyl phosphates increases with an increase in pressure at constant temperature. A reverse behavior was observed, wherein the solubilities decreased with increase in temperature in the investigated pressure region. At constant temperature and pressure, the solubilities of the trialkyl phosphates decrease with the alkyl chain length. The solubility data was found to be consistent with the Mendez–Teja model. The solubilities were correlated by the Chrastil model and an association model based on the van Laar activity coefficient model with absolute deviations of less than 10%. A key result is that the model parameters based on the association model varied linearly with the carbon number.